2019
DOI: 10.3892/ijmm.2019.4440
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of miR‑30c‑5p reduces cellular cytotoxicity and inhibits the formation of kidney stones through ATG5

Abstract: MicroRNAs (miRNAs or miRs) are critical regulators in various diseases. In the current study, the role of miR-30c-5p in the formation of sodium oxalate-induced kidney stones was investigated. For this purpose, human renal tubular epithelial cells (HK-2 cells) were incubated with sodium oxalate at the concentrations of 100, 250, 500, 750 and 1,000 µM. cell viability and the miR-30c-5p expression level were respectively measured by ccK-8 assay and RT-qPcR. After separately transfecting miR-30c-5p mimic and inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 42 publications
(37 reference statements)
0
9
0
Order By: Relevance
“…In brief, mice received intraperitoneal injection with vehicle (saline) or glyoxylate (Gly; 75 mg/kg/d; 200 μl) on days 8 through 14. Mice in TF (MCE, HY-N0243) intervention groups were daily treated with TF by gavage at three different doses (20,50, and 100 mg/kg) on days 1 through 14. Theaflavin dosages were based on two previous studies [6,27].…”
Section: Animals and Experimental Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…In brief, mice received intraperitoneal injection with vehicle (saline) or glyoxylate (Gly; 75 mg/kg/d; 200 μl) on days 8 through 14. Mice in TF (MCE, HY-N0243) intervention groups were daily treated with TF by gavage at three different doses (20,50, and 100 mg/kg) on days 1 through 14. Theaflavin dosages were based on two previous studies [6,27].…”
Section: Animals and Experimental Protocolmentioning
confidence: 99%
“…Our published paper revealed that the interaction of lncRNA H19 with miR-216b contributed to the development of CaOx nephrocalcinosis-induced oxidative stress and tubular cell injury through the regulation of HMGB1/TLR4/NF-kB signaling pathway 5 . Several studies also identified some miRNAs exerting protective effects in the formation of kidney stones, such as miR‑30c‑5p 20 , miR-93-5p 17 , miR-34a 21 , and miR-142a 22 . All in all, miRNAs work in a variety of roles in kidney stone disease.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, miR-30c-1-3p and miR-30c-5p played a negative regulatory role in xenophagy induced by H. pylori infection in GES-1 cell lines. However, studies have reported that miR-30c-5p relieves kidney stones by targeting ATG5 in human renal tubular epithelial cells [32]. More researches are needed to confirm the regulatory roles of miR-30c-1-3p and miR-30c-5p in different cell lines, tissues, organs, and even different disease processes.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, miR-103a-3p regulates the progression of both autophagy and apoptosis of cardiomyocytes through binding to ATG5 (Zhang et al, 2019b ). Previous research also showed that miR-30c-5p targets ATG5 to protect renal tubular epithelial cells against oxidative stress injury (Wang X. et al, 2020 ). Moreover, bioinformatics predicted that miR-30c-5p could target AGT5 in our preliminary study, indicating that miR-30c-5p has the potential of regulating autophagy.…”
Section: Introductionmentioning
confidence: 89%